2018
DOI: 10.1155/2018/8784750
|View full text |Cite
|
Sign up to set email alerts
|

Using the Revised Bloom Taxonomy to Analyze Psychotherapeutic Games

Abstract: Most of the scientific literature on computer games aimed at offering or aiding in psychotherapy provides little information on the relationship between the game’s design and the player’s cognitive processes. This article investigates the use of Bloom’s taxonomy in describing a psychotherapeutic game in terms of knowledge level and cognitive processing. It introduces the Revised Bloom Taxonomy and applies this to five psychotherapeutic games (Personal Investigator, Treasure Hunt, Ricky and the Spider, Moodbot,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 16 publications
0
6
0
2
Order By: Relevance
“…The example proposed as an application is about learning grammar. Where the proposed method has considered three aspects of integrated learning, namely cognitive, affective and psychomotor aspects of the player [22], [23].…”
Section: Bloom's Taxonomymentioning
confidence: 99%
See 1 more Smart Citation
“…The example proposed as an application is about learning grammar. Where the proposed method has considered three aspects of integrated learning, namely cognitive, affective and psychomotor aspects of the player [22], [23].…”
Section: Bloom's Taxonomymentioning
confidence: 99%
“…Proffer independence of movement concerning Based on the findings described above, this paper contribution is proposing online education, namely a serious-game, carried out based on the activity theory model approach, which combines the learning, game, and instructional aspects [20], [21]. It also covers the three domains of Bloom's Taxonomy [22] [23]. As an initial focus, we suggest that case studies of the science material used are Natural Science material, earth, and space sub-chapters for 4 th -grade elementary schools in Indonesia.…”
Section: Introductionmentioning
confidence: 99%
“…The authors used individual and adaptive intelligent learning systems (ITS) and, using the assessment of the results, showed that for this form of ITS there is still enough room for optimization, which is a constant method of improvement and updating in such systems. Priscilla Haring (Haring et al, 2018), examining information on the relationship between game design and player's cognitive processes, explores the use of Bloom's taxonomy in describing a psychotherapeutic game in terms of knowledge and cognitive processing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Sebagai fokus awal, kami menyarankan materi sains yang digunakan merupakan materi Ilmu Pengetahuan Alam, dengan subbab bumi dan antariksa untuk kelas empat sekolah dasar. ; 2) Serious Game yang diajukan dalam penelitian ini berbasis model Teori Aktivitas (Carvalho, 2016;Callaghan, McShane, & Eguíluz, 2018) dan melingkupi tiga ranah Taksonomi Bloom (Ahmad & Hussin, 2017;Haring, Warmelink, Valente, & Roth, 2018).…”
Section: Pendahuluanunclassified
“…Contoh yang diajukan sebagai penerapan adalah tentang pembelajaran tata bahasa. Terkait hal tersebut, desain yang diajukan sudah mempertimbangkan tiga aspek pembelajaran secara terpadu, yaitu aspek kognitif, afektif, dan psikomotorik pemain (Ahmad & Hussin, 2017;Haring, Warmelink, Valente, & Roth, 2018).…”
Section: Taksonomi Bloomunclassified